Buying Lottery Tickets for Foreign Workers: Search Cost Externalities Induced by H-1B Policy - Rishi Sharma; Chad Sparber (Institute of Labor Economics (IZA), 2020)
The H-1B program allows firms in the United States to temporarily hire high-skilled foreign citizens. H-1B workers are highly concentrated among a small number of firms. We develop a theoretical model demonstrating that this phenomenon is an artifact of policy design: When the government restricts foreign labor inflows and allocates H- 1B status by random lottery, it creates a negative externality by incentivizing firms to search for more workers than can actually be hired. Some firms rationally move toward specializing in hiring foreign labor and contracting out those workers' services to third- party sites. This outsourcing behavior further exacerbates total search costs and lottery externalities, resulting in an annual economic loss in the hundreds of millions of dollars.
Keywords: J61; J68; F22; 330; skilled workers; H-1B; outsourcing